PERHITUNGAN NILAI MANFAAT DAN BIAYA MIGRASI INTERNASIONAL TENAGA KERJA INDONESIA - Adhisti, Mita (Jurnal Ekonomi & Studi Pembangunan, 2014)
Abstract: The low employment and the standard wage or salary in the country into individual driving factors for migrating abroad to find work. This study specifically addresses the calculation of benefits gained migrant workers during their working lives and costs to be incurred during the placement process in South Korea, Malaysia, Singapore, and Taiwan. The calculation of the estimated value of net benefits is the result of a reduction in the value of benefits and costs, referring to the model of the value of the benefits and costs of international migration developed by Massey et al (1993) The results of calculations indicate that the estimated net benefits received by migrant workers in South Korea and Taiwan during the three-year period amounted to 234.5 and 130.8 million. As for the working period of two years, the estimated net value of the benefit received TKI Singapore and Malaysia amounted to 48.5 million and 39 million. The results of the calculations can be used as an alternative choice in the decision making process of individuals to choose the destination country of employment. Abstrak: Rendahnya kesempatan kerja maupun standar upah atau gaji di dalam negeri menjadi faktor pendorong individu untuk migrasi ke luar negeri untuk mendapatkan kerja. Studi ini secara khusus membahas perhitungan manfaat yang didapatkan TKI selama masa kerjanya dan biaya yang harus dikeluarkan selama mengikuti proses penempatan di Korea Selatan, Malaysia, Singapura, dan Taiwan. Perhitungan estimasi nilai manfaat bersih yang merupakan hasil pengurangan antara nilai manfaat dan biaya, mengacu pada model nilai manfaat dan biaya migrasi internasional yang dikembangkan oleh Massey et al (1993).Hasil perhitungan menunjukkan bahwa estimasi manfaat bersih yang diterima TKI yang bekerja di Korea Selatan dan Taiwan selama masa kerja tiga tahun adalah sebesar 234,5 dan 130,8 juta rupiah. Sedangkan untuk masa kerja dua tahun, estimasi nilai manfaat bersih yang diterima TKI Singapura dan Malaysia sebesar 48,5 juta rupiah dan 39 juta rupiah. Hasil perhitungan dapat digunakan sebagai pilihan alternatif dalam proses pengambilan keputusan individu untuk memilih negara tujuan kerja.